Paradoxical aortic stiffening and subsequent cardiac dysfunction in Hutchinson–Gilford progeria syndrome. Issue 166 (27th May 2020) - Murtada, S.-I.; Kawamura, Y.; Caulk, A. W.; Ahmadzadeh, H.; Mikush, N.; Zimmerman, K.; Kavanagh, D.; Weiss, D.; Latorre, M.; Zhuang, Z. W.; Shadel, G. S.; Braddock, D. T.; et al.
Abstract : Hutchinson–Gilford progeria syndrome (HGPS) is an ultra-rare disorder with devastating sequelae resulting in early death, presently thought to stem primarily from cardiovascular events. We analyse novel longitudinal cardiovascular data from a mouse model of HGPS ( Lmna G609G/G609G ) using allometric scaling, biomechanical phenotyping, and advanced computational modelling and show that late-stage diastolic dysfunction, with preserved systolic function, emerges with an increase in the pulse wave velocity and an associated loss of aortic function, independent of sex. Specifically, there is a dramatic late-stage loss of smooth muscle function and cells and an excessive accumulation of proteoglycans along the aorta, which result in a loss of biomechanical function (contractility and elastic energy storage) and a marked structural stiffening despite a distinctly low intrinsic material stiffness that is consistent with the lack of functional lamin A. Importantly, the vascular function appears to arise normally from the low-stress environment of development, only to succumb progressively to pressure-related effects of the lamin A mutation and become extreme in the peri-morbid period. Because the dramatic life-threatening aortic phenotype manifests during the last third of life there may be a therapeutic window in maturity that could alleviate concerns with therapies administered during early periods of arterial development.